Identification of gene fragments related to nitrogen deficiency in Eichhornia crassipes (Pontederiaceae) - Fu, Minghui (Universidad de Costa Rica, 2014)
Eichhornia crassipes is an aquatic plant native to the Amazon River Basin. It has become a serious weed in freshwater habitats in rivers, lakes and reservoirs both in tropical and warm temperate areas worldwide. Some research has stated that it can be used for water phytoremediation, due to its strong assimilation of nitrogen and phosphorus, and the accumulation of heavy metals, and its growth and spread may play an important role in environmental ecology. In order to explore the molecular mechanism of E. crassipes to responses to nitrogen deficiency, we constructed forward and reversed subtracted cDNA libraries for E. crassipes roots under nitrogen deficient condition using a suppressive subtractive hybridization (SSH) method. The forward subtraction included 2 100 clones, and the reversed included 2 650 clones. One thousand clones were randomly selected from each library for sequencing. About 737 (527 unigenes) clones from the forward library and 757 (483 unigenes) clones from the reversed library were informative. Sequence BlastX analysis showed that there were more transporters and adenosylhomocysteinase-like proteins in E. crassipes cultured in nitrogen deficient medium; while, those cultured in nitrogen replete medium had more proteins such as UBR4-like e3 ubiquitin-protein ligase and fasciclin-like arabinogalactan protein 8-like, as well as more cytoskeletal proteins, including actin and tubulin. Cluster of Orthologous Group (COG) analysis also demonstrated that in the forward library, the most ESTs were involved in coenzyme transportation and metabolism. In the reversed library, cytoskeletal ESTs were the most abundant. Gene Ontology (GO) analysis categories demonstrated that unigenes involved in binding, cellular process and electron carrier were the most differentially expressed unigenes between the forward and reversed libraries. All these results suggest that E. crassipes can respond to different nitrogen status by efficiently regulating and controlling some transporter gene expressions, certain metabolism processes, specific signal transduction pathways and cytoskeletal construction.